Social cleavages and political conflicts in the contemporary Czech society - Pavel Machonin (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
There are a number of significant social cleavages and political conflicts within the population of the European postsocialist societies. The first one concerns the cleavage between the decreasing number of people who benefited from the “Ancien régime” and those who took advantage of the new developments over the past 12 years. The second one concerns cleavages based on ethnic differences, which are more important in South Eastern than in Central Europe. The third cleavage is the rapid polarization between the rich and the poor, which developed in the relatively egalitarian Czech social structure as a consequence of the rapid privatization and the sudden liberalization of both the economy and other spheres of life. These cleavages as well as some other conflicts influence the contemporary existing political relationships which – under Czech circumstances – are characterized by a relative balance of four main political currents. The optimal solution for the hybrid coexistence of these cleavages and conflicts would consist in strengthening the role of forces which are important for the development analogously to the more advanced postindustrial European models of social and political arrangements.
Keywords: 300; Sozialer Konflikt; Übergangswirtschaft; Tschechische Republik; Politische Stabilität